Impact of Chronic Pain on Treatment Prognosis for Patients with Opioid Use Disorder: A Systematic Review and Meta-analysis - Brittany B. Dennis; Monica Bawor; Leen Naji; Carol K. Chan; Jaymie Varenbut; James Paul; Michael Varenbut; Jeff Daiter; Carolyn Plater; Guillaume Pare; David C. Marsh; Andrew Worster; et al. (SAGE Publishing, 2015)
Background While a number of pharmacological interventions exist for the treatment of opioid use disorder, evidence evaluating the effect of pain on substance use behavior, attrition rate, and physical or mental health among these therapies has not been well established. We aim to evaluate these effects using evidence gathered from a systematic review of studies evaluating chronic non-cancer pain (CNCP) in patients with opioid use disorder. Methods We searched the Medline, EMBASE, PubMed, PsycINFO, Web of Science, Cochrane Database of Systematic Reviews, ProQuest Dissertations and theses Database, Cochrane Central Register of Controlled Trials, World Health Organization International Clinical Trials Registry Platform Search Portal, and National Institutes for Health Clinical Trials Registry databases to identify articles evaluating the impact of pain on addiction treatment outcomes for patients maintained on opioid agonist therapy. Results Upon screening 3,540 articles, 14 studies with a combined sample of 3,128 patients fulfilled the review inclusion criteria. Results from the meta-analysis suggest that pain has no effect on illicit opioid consumption [pooled odds ratio (pOR): 0.70, 95%CI 0.41-1.17; I 2 = 0.0] but a protective effect for reducing illicit non-opioid substance use (pOR: 0.57, 95%CI 0.41-0.79; I 2 = 0.0). Studies evaluating illicit opioid consumption using other measures demonstrate pain to increase the risk for opioid abuse. Pain is significantly associated with the presence of psychiatric disorders (pOR: 2.18; 95%CI 1.6, 2.9; I 2 = 0.0%). Conclusion CNCP may increase risk for continued opioid abuse and poor psychiatric functioning. Qualitative synthesis of the findings suggests that major methodological differences in the design and measurement of pain and treatment response outcomes are likely impacting the effect estimates.